Production Of Antimicrobial And Bioactive Peptides From Bakasam Using Enterococcus Faecium 1.15 As A Starter - Setiyadi Putranto, Wendry; Gumilar, Jajang; Wulandari, Eka; Pratama, Andry; Mamangkey, Jendri (Publisher Cv. Inara, 2023)
The Development Of Traditional Fermented Food Products Into Functional Food, Utilizing Indigenous Microorganisms, Represents A Novel Innovation. Lactic Acid Bacteria (Lab), Which Are Abundantly And Readily Isolated From Native Fermented Foods, Hold Promise For The Exploration Of Local Lab Strains – A Strategic Step Towards The Development Of ProbioticBased Foods In Indonesia. Enterococcus Faecium 1.15 Isolated From Bakasam Beef, Has Demonstrated The Capability To Produce Extracellular Proteases (4.83 U/Mg) And Displayed Inhibitory Effects Against Pathogenic Bacteria. The Production Of Bioactive Peptides, With A Size Less Than 30 Kda, Could Be Achieved Through Bakasam Fermentation Using E. Faecium 1.15 As A Starter For A Period Of 7 Days. This Study Promotes An Opportunity To Harness Local Microorganisms, Particularly Lab Strains In The Utilization Of Bioactive Peptides As Well As Enhancing The Nutritional Value Of Traditional Fermented Foods.